2016
DOI: 10.1007/s10815-016-0733-1
|View full text |Cite
|
Sign up to set email alerts
|

Collection of pregnancy outcome records following infertility—challenges and possible solutions

Abstract: Collecting records is time-consuming but important as over 50 % of our participants received care outside of the home facility. To efficiently collect outside records, we recommend that researchers interested in maternal and neonatal outcomes consider the guidelines outlined in this manuscript. This report also provides strong evidence of the need to develop data sharing through electronic health records for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Participants were part of the Stanford Pregnancy Outcomes Following Infertility (POFI) Study (19). After approval of the study by the institutional review board at Stanford University, 878 infertile patients undergoing treatment at the Stanford Division of Reproductive Endocrinology and Infertility with sonographically confirmed viable pregnancy were recruited at 8 weeks' gestation between October 2011 and March 2014.…”
Section: Stanford Pregnancy Outcomes Following Infertility Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were part of the Stanford Pregnancy Outcomes Following Infertility (POFI) Study (19). After approval of the study by the institutional review board at Stanford University, 878 infertile patients undergoing treatment at the Stanford Division of Reproductive Endocrinology and Infertility with sonographically confirmed viable pregnancy were recruited at 8 weeks' gestation between October 2011 and March 2014.…”
Section: Stanford Pregnancy Outcomes Following Infertility Studymentioning
confidence: 99%
“…Accordingly, the first aim of this study was to investigate maternal RAAS determinants in early pregnancy. To address this question, we used 2 large periconception cohorts, the Stanford Pregnancy Outcomes Following Infertility (POFI) Study and the Rotterdam Periconceptional Cohort (Predict) Study (19,20). Importantly, von Versen-Höynck et al have shown in the POFI Study that an abnormal CL number associates with increased preeclampsia risk (14).…”
mentioning
confidence: 99%
“…Finally, our study may face challenges in the retrieval of medical records for outcome ascertainment. Acceptance of medical release forms, timeliness of delivery, responsiveness of obstetrical offices, and receiving hospitals are a few of the anticipated problems [ 36 ]. Through trimester contacts, we hope to supplement medical record data and decrease loss to follow-up by gathering clinical data through structured questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…As evident in the supplemental analysis, the study was potentially underpowered to detect significant differences in outcomes such as clinical pregnancy rates until the “Low E2” sample size increased with a higher E2 cutoff. The lack of a unified medical record system in the United States poses a significant challenge to accessing detailed pregnancy and neonatal medical records for a larger cohort of women who have undergone LTZ-FETs ( 57 ). Most of the patients in our cohort were Asian and Caucasian, potentially limiting the generalizability to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%